2020
DOI: 10.1186/s13023-019-1287-y
|View full text |Cite
|
Sign up to set email alerts
|

Management and current status of spinal muscular atrophy: a retrospective multicentre claims database analysis

Abstract: Introduction: The interest in patient demographics and disease management has increased in the past years due to their utility in developing measures that allow healthcare providers to reflect disease complexity. Objective: To revise the current status of spinal muscular atrophy in the region of Catalonia, and to validate the utility of the database for this aim. Methods: Five hundred twenty-four patients diagnosed with a spinal muscular atrophy were identified in the region of Catalonia via the novel program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
1
8
0
2
Order By: Relevance
“…This is particularly detrimental in neutrophils since their energy metabolism depends almost entirely on glycolysis. Treatment with a sodium-glucose transport protein subtype 2 (SGLT2) inhibitor released the blockage and allowed neutrophil maturation [ 50 ]. Five GSDIb patients (3 children and 2 adults) were treated with a SGLT2 inhibitor and improved their heterogeneous clinical findings related to neutrophil dysfunction [ 50 , 51 ].…”
Section: Markers Found In Von Gierke Disease (Gsdi)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly detrimental in neutrophils since their energy metabolism depends almost entirely on glycolysis. Treatment with a sodium-glucose transport protein subtype 2 (SGLT2) inhibitor released the blockage and allowed neutrophil maturation [ 50 ]. Five GSDIb patients (3 children and 2 adults) were treated with a SGLT2 inhibitor and improved their heterogeneous clinical findings related to neutrophil dysfunction [ 50 , 51 ].…”
Section: Markers Found In Von Gierke Disease (Gsdi)mentioning
confidence: 99%
“…Treatment with a sodium-glucose transport protein subtype 2 (SGLT2) inhibitor released the blockage and allowed neutrophil maturation [ 50 ]. Five GSDIb patients (3 children and 2 adults) were treated with a SGLT2 inhibitor and improved their heterogeneous clinical findings related to neutrophil dysfunction [ 50 , 51 ]. Based on this, 1,5AG could be a good candidate to be a biomarker for treating neutropenia in GSDIb and G6PC3-deficient patients.…”
Section: Markers Found In Von Gierke Disease (Gsdi)mentioning
confidence: 99%
“…The publications comprised data from 14 countries, including the USA (n = 20) [48-50, 53, 54, 56, 57, 60, 63, 70, 74, 77, 80, 84-86, 88, 91-93], UK (n = 5) [52,68,81,89,98], Italy (n = 2) [59,83], Australia (n = 2) [64,71], Canada (n = 1) [75], Germany (n = 1) [55], Croatia (n = 1) [87], Korea (n = 1) [65], Japan (n = 1) [66], France (n = 1) [79], Spain (n = 4) [58,72,73,78], Sweden (n = 1) [61], Russia (n = 2) [94,97] and Turkey (n = 1) [96]. Seven studies reported multi-national data [62,67,69,76,82,90,95].…”
Section: Description Of Identified Studiesmentioning
confidence: 99%
“…Cost drivers (factors that create or drive the cost of management) associated with SMA were reported in 28 studies [50, 53-61, 64, 68, 70-79, 83-85, 92, 94, 97]. Major cost drivers included the requirement for inpatient care (n = 22) [50, 53-56, 58, 60, 68, 70-74, 76-79, 84, 85, 92, 94, 97], use of outpatient services or specialist visits (n = 16) [50, 53-55, 58-60, 70-74, 76, 78, 84, 85], respiratory care (n = 10) [50,54,55,57,61,70,71,73,78,83], rehabilitation (n = 4) [50,55,79,97], orthopaedic care (n = 2) [61,83], prescription costs (excluding DMT-related costs) [n = 8] [50, 53,58,60,74,76,77,84], home stays (n = 3) [58,70,79] and structural changes to the house or car (n = 6) [55,59,60,64,71,75]. One study reported cost drivers to be type dependent, with Type 1 SMA costs driven by respiratory care, and Types 2 and 3 SMA costs driven by orthopaedic care [83].…”
Section: Cost Driversmentioning
confidence: 99%
See 1 more Smart Citation